2013
DOI: 10.2147/ijn.s39642
|View full text |Cite
|
Sign up to set email alerts
|

Changes in urinary nanocrystallites in calcium oxalate stone formers before and after potassium citrate intake

Abstract: Abstract:The property changes of urinary nanocrystallites in 13 patients with calcium oxalate (CaOx) stones were studied before and after ingestion of potassium citrate (K 3 cit), a therapeutic drug for stones. The analytical techniques included nanoparticle size analysis, transmission electron microscopy, X-ray diffraction, and Fourier-transform infrared spectroscopy. The studied properties included the components, morphologies, zeta potentials, particle size distributions, light intensity autocorrelation cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Thus, the morphological characteristic assumed by COM crystals after incubation with C. cupressoides SPs is advantageous, as, by leaving the edges of their faces with a slight angle (rounded), the possible interaction of these crystals in renal epithelium could be decreased, which would consequently favor their passage in the urinary tract, thus reducing the formation of kidney stones. In agreement with our hypothesis, studies analyzing CaOx crystals in the urine of lithogenic patients verified that the COM crystals had edges and tips with sharp angles and concluded that these are important factors for the anchorage of these crystals in the renal epithelium [30,33].…”
Section: Resultssupporting
confidence: 85%
“…Thus, the morphological characteristic assumed by COM crystals after incubation with C. cupressoides SPs is advantageous, as, by leaving the edges of their faces with a slight angle (rounded), the possible interaction of these crystals in renal epithelium could be decreased, which would consequently favor their passage in the urinary tract, thus reducing the formation of kidney stones. In agreement with our hypothesis, studies analyzing CaOx crystals in the urine of lithogenic patients verified that the COM crystals had edges and tips with sharp angles and concluded that these are important factors for the anchorage of these crystals in the renal epithelium [30,33].…”
Section: Resultssupporting
confidence: 85%
“…Moreover, the submicron particle identified with electron microscopy lack the characteristic cup shape of exosomes. Further, the increase in size was inhibited by the addition of the chelator citrate, which has also been reported to help inhibit urinary crystallite deposition and CaOx stone formation[37]. …”
Section: Discussionmentioning
confidence: 99%
“…It is reported that calcium oxalate monohydrate (COM) is involved in hyperoxaluria, while calcium oxalate dihydrate (COD) is related to hypercalciuria [9]. The CaOx formation process comprises nucleation, development, clustering, and cell adhesion [10,11]. CaOx stones frequently possess a core-shell structure.…”
Section: Introductionmentioning
confidence: 99%